Complications, patient-reported outcomes, and aesthetic results in immediate breast reconstruction with a dermal sling: A systematic review and meta-analysis. Issue 3 (March 2019) - Jepsen, Christian; Hallberg, Håkan; Pivodic, Aldina; Elander, Anna; Hansson, Emma
Summary: An inferior dermal flap ("sling") can be used to cover an implant with two layers of tissue following Wise pattern skin-reducing mastectomies. Here, we performed a systematic review of the risks and benefits of this technique, specifically regarding complications, patient-reported outcomes, and aesthetic outcomes. PubMed and other relevant databases were searched using specific key words, with inclusion criteria comprising studies of dermal sling use involving ≥ 5 patients and performance according to the PICO framework. A meta-analysis was performed using a random-effects model involving a binomial distribution with logit-link function. For each study, the 95% confidence interval (CI) was obtained based on exact limits from a binomial distribution, and heterogeneity testing was performed using a chi-squared test. A total of 428 abstracts were retrieved, with 24 studies meeting the inclusion criteria and including a total of 879 patients and 1184 reconstructed breasts. The mean complication rate was 21.6% (95% CI: 16.9–27.2%), with the most common complication involving wound-healing problems (mean, 11.4%; 95% CI: 8.5–15.2%), and the frequency of implant loss (< 3 months) varied from 0% to 14% (mean, 2.2%; 95% CI: 1.1–4.4%). Seven articles reported patient-reported outcomes, and four reported aesthetic outcomes, with the quality of evidence classified as low for complications and very low for patient-reported outcomes and aesthetic outcomes. Our findings showed that although implant-based reconstruction with a dermal sling is widely used, there is little scientific evidence supporting the method.